The battle between the innate immune cGAS-STING signaling pathway and human herpesvirus infection - Jin, Ximing; Wang, Wenjia; Zhao, Xinwei; Jiang, Wenhua; Shao, Qingqing; Chen, Zhuo; Huang, Cong (Frontiers in Immunology, 2023)
The incidence of human herpesvirus (HHVs) is gradually increasing and has affected a wide range of population. HHVs can result in serious consequences such as tumors, neonatal malformations, sexually transmitted diseases, as well as pose an immense threat to the human health. The cGAS-STING pathway is one of the innate immune pattern-recognition receptors discovered recently. This article discusses the role of the cGAS-STING pathway in human diseases, especially in human herpesvirus infections, as well as highlights how these viruses act on this pathway to evade the host immunity. Moreover, the author provides a comprehensive overview of modulators of the cGAS-STING pathway. By focusing on the small molecule compounds based on the cGAS-STING pathway, novel targets and concepts have been proposed for the development of antiviral drugs and vaccines, while also providing a reference for the investigation of disease models related to the cGAS-STING pathway. HHV is a double-stranded DNA virus that can trigger the activation of intracellular DNA sensor cGAS, after which the host cells initiate a cascade of reactions that culminate in the secretion of type I interferon to restrict the viral replication. Meanwhile, the viral protein can interact with various molecules in the cGAS-STING pathway. Viruses can evade immune surveillance and maintain their replication by inhibiting the enzyme activity of cGAS and reducing the phosphorylation levels of STING, TBK1, and IRF3 and suppressing the interferon gene activation. Activators and inhibitors of the cGAS-STING pathway have yielded numerous promising research findings in vitro and in vivo pertaining to cGAS-STING-related disease models. However, there remains a dearth of small molecule modulators that have been successfully translated into clinical applications, which serves as a hurdle to be overcome in the future.